ANALISIS KEPUASAN NASABAH ATAS KUALITAS LAYANAN INTERNET BANKING PADA PT BANK PEMBANGUNAN DAERAH JAWA TENGAH KANTOR CABANG PATI - Anita Elvi Mutiasari; Embun Duriany Soemarso (KEUNIS, 2020)
This research aims to identify how to increase customer satisfaction of internet banking service quality at PT Bank Pembangunan Daerah Jawa Tengah Pati Branch Office with five dimensions of service quality which were tangible, reliability, responsiveness, assurance, and empathy.In this research, the sampling technique used was purposive sampling technique. The data in this research were obtained from observations and distributing questionnaires to 100 respondents. Data analysis methods used are validity test, reliability test, satisfaction index test, satisfaction gap test and satisfaction mapping with cartesian diagram.Based on the result of the validity and reliability test, the indicators like tangible, reliability, responsiveness, assurance and empathy are valid and reliable. Based on the result of the satisfaction index analysis, the weighting score of internet banking quality service is 4,219. That score is between 3,43 – 4,23 wich means Satisfied. Based on the result of the satisfaction gap test the increase of satisfaction established on the fourteen sub-indicators show satisfaction, and four sub-indicators show dissatisfaction. Meanwhile, when viewed from the cartesian diagram mapping result, there are four indicators that fall into the quadrant I, four indicators in the quadrant II, four indicators in the quadrant III, and six indicators in the quadrant IV.